Suitability of pulse intercrops during autumn planted sugarcane through trench method - Yadav, Shriprakash (Annals of Agricultural Research, 2018)
A field experiment was conducted during 2011-13 and 2012-14 in autumn at research farm of U.P. Council of Sugarcane Research, Shahjahanpur, (U.P.) to work out the response of inter-crops and its residual effect along with different nitrogen doses on trench planted sugarcane. The experimental soil was sandy loam in texture, low in organic carbon (0.36%), available nitrogen (260kg/ha), medium in available phosphorus (11.43 kg/ha) and potassium (124 kg/ha) with the pH value 7.7. Soil test based fertilizer recommendation per hectare was 200 kg N + 80 kg P2O5 + 60 kg K2O. CoSe 01434 a mid - late maturing variety of sugarcane was tested with inter - crops like Azad pea - 1 and berseem Mescavi - 530 varieties. Among different inter - cropping systems and nitrogen doses (100% and 125% RD - N), cane + berseem along with 125% nitrogen dose through inorganics was found to be much beneficial and gave significantly higher cane yield (114.6 t/ha) than the cane planted alone in trench (107.6 t/ha). This treatment improved the cane yield by 6.06% and reflected a higher B:C ratio of 2.22 against cane alone (1.90). The inter - crop viz., Pea followed after berseem. Effect of these pulses inter - cropping on juice quality parameters was not significant.